Numerical Investigation for the Design of a Hot Forging Die with Integrated Cooling Channels. (2016) - Behrens, B.-A.; Bouguecha, A.; Vucetic, M.; Bonhage, M.; Malik, I.Y.
Abstract: Ongoing research at the Institute of Forming Technology and Machines (IFUM) within the scope of sub-project E3 of the Collaborative Research Centre 653 deals with the generation of controlled cavities inside a sintered hot forging die. The primary objective of sub-project E3 is to develop a forging die which can "feel", "learn" and "control" autonomous reactions to process variations. The current project stage aims at developing a hot forging die with integrated cooling channels. This paper presents the findings of numerical investigations carried out to analyze the hot forging die made of tool steel powder and equipped with internal cooling channels. Two different geometric variations have been numerically investigated in order to study the stress states within the die under process boundary conditions.